Alloimmunity in pancreas transplantation. Issue 4 (August 2020) - Aziz, Fahad; Mandelbrot, Didier; Parajuli, Sandesh; Al-Qaoud, Talal; Redfield, Robert; Kaufman, Dixon; Odorico, Jon S.
Abstract : Purpose of review: Despite significant improvement in pancreas allograft survival, rejection continues to be a major clinical problem. This review will focus on emerging literature related to the impact of pretransplant and de-novo DSA (dnDSA) in pancreas transplant recipients, and the diagnosis and treatment of T-cell-medicated rejection (TCMR) and antibody-mediated rejection (ABMR) in this complex group of patients. Recent findings: Recent data suggest that pretransplant DSA and the emergence of dnDSA in pancreas transplant recipients are both associated with increased risk of ABMR. The pancreas allograft biopsy is essential for the specific diagnosis of TCMR and/or ABMR, distinguish rejection from other causes of graft dysfunction, and to guide-targeted therapy. This distinction is important especially in the setting of solitary pancreas transplants but also in simultaneous pancreas-kidney transplants where solid evidence has now emerged demonstrating discordant biopsy findings. Treatment of rejection in a functioning pancreas can prolong allograft survival. Summary: The accurate and timely diagnosis of active alloimmune destruction in pancreas transplant recipients is paramount to preserving graft function in the long term. This review will discuss new, rapidly evolving information that is valuable for the physician caring for these patients to achieve optimal immunological outcomes.